MODEL NUMERIK 2-D (LATERAL & LONGITUDINAL) SEBARAN POLUTAN CADMIUM(Cd) DI MUARA SUNGAI (STUDI KASUS: MUARA SUNGAI BABON, SEMARANG) - Badrus Zaman; Syafrudin Syafrudin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Estuary of River Babon very influenced by condition around its drainage basin. estuary of River Babon  also have  function  as  a  channel  of  waste  disposal  from  Terboyo  Industrial  Park, Semarang ( KITS). Cadmium ( Cd) as one of heavy metal pollutant and conservative element will certainly spread at estuarine. Based on research at the time of measurement, known that by the  content  of  Cd  at  estuary of  river  Babon  equal  to  (  0,009  -  0,017)  mg  /  l,  where  the concentration have exceeded the Quality of Water Go out to sea for the Biota of Go out to sea that  is  equal  to  0.001  mg  /  l  (Kep Men LH  No.  51  tahun  2004).    Study  about  disseminating polutan  at  estuarine  can  be  conducted  by using  model    because  by  using  model  can  be knowable  how  disseminating  polutan  accurately, quickly  and  cheap  so  that  picture  from  the model can be made basis for furthermore management. Model developed with numerical 2-D model ( lateral & longitude). Model developed by using equation on the basis of hydrodynamics process  and  conservative  transpor  polutan.  The  equation  finished  by numerik  by  using differential method ( finite difference). The result from developed model for the time of t = 1 hour obtained value with 3.028% mistake from field data.